Differences between amyloid-β aggregation in solution and on the membrane: Insights towards elucidation of the mechanistic details of Alzheimer’s disease - Kotler, Samuel A. (2014)
The association of the amyloid-β (Aβ) peptide with cellular membranes is hypothesized to be the underlying phenomenon of neurotoxicity in Alzheimer’s disease. Misfolding of proteins and peptides, as is the case with Aβ, follows a progression from a monomeric state, through intermediates, ending at long, unbranched amyloid fibers. This tutorial review offers a perspective into the association of toxic Aβ structures with membrane as well as details into membrane-associated mechanisms of toxicity.